2D Thin Nanoflakes Assembled on Mesoporous Carbon Nanorods for Enhancing Electrocatalysis and for Improving Asymmetric Supercapacitors. (31st August 2016) - Shang, Pei; Zhang, Jianan; Tang, Wanyu; Xu, Qun; Guo, Shaojun
Abstract : Carbon nanomaterials are of great interest as the advanced supports of electrochemical active materials to enhance their performances, however, little knowledge has been put into understanding whether the pores of carbon nanomaterials as supports can tune the performance of energy storage and conversion devices due to the lack of methods for making porous carbon nanomaterials. Herein, this study demonstrates the use of 1D ordered mesoporous carbon nanorods (OMCRs) with high surface area as a new class of supports for 2D ultrathin MoS2 and MnO2 nanoplates to create the interesting hierarchical nanohybrids (MoS2 @OMCRs and MnO2 @OMCRs), respectively. With the significant role of OMCRs in optimizing the electron and charge transportation, MoS2 @OMCRs exhibits remarkable activity for catalyzing hydrogen evolution reaction with a low onset overpotential of 105 mV and low Tafel slope of 40 mV dec −1, much better than those of MoS2 @ carbon nanofibers. Significantly, the asymmetric supercapacitor based on MnO2 @OMCRs as anode and OMCRS as cathode displays a maximum specific capacitance up to 100 F g −1 at 0.2 A g −1 and a high energy density of 55.2 W h kg −1 at the power density of 200 W kg −1 within a wide operating voltage of 2.0 V. The present work highlights the important role of the mesoporous carbon support in achieving the advanced energy storage and conversion. Abstract : 2D ultrathin nanoplates are successfully decorated on the surface of 1D ordered mesoporous carbon nanorods for boosting hydrogen evolution reaction catalysis and asymmetric supercapacitor performance.